2023
DOI: 10.1007/s00784-023-05120-0
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional and positional temporomandibular joint osseous characteristics in normodivergent facial patterns with and without temporomandibular disorders

Abstract: Objective This study evaluated the dimensional and positional osseous temporomandibular joint features in normodivergent facial patterns with and without temporomandibular disorders. Methods A total of 165 adult patients were divided into two groups: group 1 (n = 79 patients; 158 joints): temporomandibular disorders patients and group 2 (n = 86 patients; 172 joints): non-temporomandibular disorders patients. Three-dimensional positional and dimensional tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
1
2
1
Order By: Relevance
“…As a result of a displaced disc, the condyle will vertically adjust itself to fill that space occupied by the disc; furthermore, it moved downward forward and medially post-treatment T1, leading to the upward and lateral position of the contralateral side (contributing to MA improvement). The findings of T0 are in agreement with the findings of Alhammadi et al [ 41 ], who reported that the condyle was in superior, posterior, and lateral positions, while Akahane et al [ 38 ] suggested upward positioning. The findings of T1 are in agreement with [ 26 , 30 , 42 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…As a result of a displaced disc, the condyle will vertically adjust itself to fill that space occupied by the disc; furthermore, it moved downward forward and medially post-treatment T1, leading to the upward and lateral position of the contralateral side (contributing to MA improvement). The findings of T0 are in agreement with the findings of Alhammadi et al [ 41 ], who reported that the condyle was in superior, posterior, and lateral positions, while Akahane et al [ 38 ] suggested upward positioning. The findings of T1 are in agreement with [ 26 , 30 , 42 ].…”
Section: Discussionsupporting
confidence: 90%
“…Mechanisms such as VEGF protein overexpression and oxidative stress/nitric oxide imbalance may contribute to unbalanced TMJ loading [ 50 ]. However, there were no statistically significant differences in FH, contrasting with findings by Alhammadi et al in TMD and non-TMD patients [ 41 ].…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…JSs, observed in radiographic images, are located in the temporal bone and mandibular condyle and constitute the spaces in which the disks reside [12]. While studies utilizing JS imaging have compared TMD patients to healthy individuals and different types of TMD [7,12,13], no studies have explored changes in JS over time in patients with TMJ OA. Therefore, this study aimed to evaluate JS changes using CBCT images of patients diagnosed with TMJ OA and determine the association between occlusal changes and JS.…”
Section: Introductionmentioning
confidence: 99%